Federalismo realocativo: sobre-representação legislativa e gastos públicos no hemisfério ocidental - Gibson, Edward L. (2015)
Este artigo trata da economia política do federalismo e a questão básica examinada é se a sobre-representação de territórios (estados e províncias) nas legislaturas nacionais dos sistemas federais afeta a distribuição territorial dos gastos públicos dos governos federais. A hipótese testada é que afeta e a sobre-representação territorial produz uma distorção dos gastos federais que beneficia as populações que vivem em territórios sobrerepresentados. Para captar essa conexão entre sobre-representação territorial e a distribuição não-proporcional de fundos públicos foi introduzida uma distinção conceitual: os países em que essa conexão existe são identificados como casos de federalismo realocativo, enquanto que os países com padrões territoriais de gastos públicos que são proporcionais à população são identificados como casos de federalismo proporcional. Os argumentos baseiam-se em dados subnacionais dos quatro maiores países federais do hemisfério ocidental: Estados Unidos, Brasil, México e Argentina. AbstractThis article is an inquiry into the political economy of federalism and the basic question explored is, does the overrepresentation of territories (states or provinces) in national legislatures of federal systems affect the territorial distribution of public spending by federal governments? The hypothesis to be tested is that it does, and that territorial overrepresentation produces a distortion of federal spending which benefits the population that live in overrepresented territories. To capture this connection it was introduced a conceptual distinction between territorial overrepresentation and the non-proportional distribution of public funds: countries where this connection exists are identified as cases of reallocative federalism, whereas countries with territorial patterns of public spending that are proportional to population are identified as cases of proportional federalism. The evidence is drawn from subnational-level data (at the provincial/state level) from the Western Hemisphere’s four largest federal countries, the United States of America, Brazil, Mexico, and Argentina. benefits populations living in overrepresented territories.Keywords: federalism, political representation, public expenditures, territory, proporcional system